Accelerated Rejection of Renal Allografts From Brain-Dead Donors - Pratschke, Johann (2000)
OBJECTIVE: To define the potential influences of donor brain death on organs used for transplantation. SUMMARY BACKGROUND DATA: Donor brain death causes prompt upregulation of inflammatory mediators on peripheral organs. It is hypothesized that this antigen-independent insult may influence the rate and intensity of host alloresponsiveness after engraftment. METHODS: The rates of survival of unmodified Lew recipients sustained by kidney allografts from brain-dead, normal anesthetized, and anesthetized ventilated F344 donors were compared. Brain death was induced by gradually increasing intracranial pressure under electroencephalographic control. Tracheotomized brain-dead animals and anesthetized controls were mechanically ventilated for 6 hours before transplant nephrectomy. The rate and intensity of the acute rejection event were examined by histology, immunohistology, and reverse transcriptase–polymerase chain reaction. RESULTS: Animals bearing kidneys from brain-dead donors died of renal failure secondary to acute rejection at a significantly faster rate than those from anesthetized living controls or anesthetized animals ventilated for 6 hours. Within 3 hours after placement and reperfusion of brain-dead donor grafts, significant neutrophil infiltration was observed, followed by increasing numbers of macrophages and T cells. mRNA of proinflammatory mediators detected in kidneys within 6 hours of brain death and upregulated even before transplantation increased thereafter and appeared to accelerate and amplify host alloresponsiveness, as manifested by the rapid expression of chemokines, cytokines, adhesion molecules, and major histocompatibility complex class II antigens in the engrafted organ. The process evolved in the controls less intensely and at a slower rate. CONCLUSIONS: Donor brain death is a significant risk factor for peripheral organs used for transplantation. The activated state of such organs appears to trigger host immune mechanisms that accelerate the process of acute rejection. The effects of this central injury may explain in part the less satisfactory performance of cadaver organs in human transplantation compared with those from living sources.